2001
DOI: 10.1002/mus.1179
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit recruitment during lengthening contractions of human wrist flexors

Abstract: The purpose of this study was to revisit the question of recruitment of motor units during lengthening contractions because of conflicting views in the literature on this subject. Motor unit activity was recorded from the flexor carpi radialis muscle of four human subjects to compare the patterns of recruitment during lengthening and isometric contractions. Lengthening contractions were produced either when the subject voluntarily stopped opposing a background load or when an additional load was imposed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
(24 reference statements)
1
28
0
1
Order By: Relevance
“…Therefore, it is possible that this selective activation may arise through the reciprocal inhibitory pathway between antagonist motor units. It must be acknowledged, however, that although the preferential activation of high threshold motor units has been proposed during lengthening actions (Nardone and Schieppati 1988), similar experiments investigating motor unit recruitment during functional activities have failed to find evidence of a reversal of recruitment order (Jones et al 1994;Stotz and Bawa 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is possible that this selective activation may arise through the reciprocal inhibitory pathway between antagonist motor units. It must be acknowledged, however, that although the preferential activation of high threshold motor units has been proposed during lengthening actions (Nardone and Schieppati 1988), similar experiments investigating motor unit recruitment during functional activities have failed to find evidence of a reversal of recruitment order (Jones et al 1994;Stotz and Bawa 2001).…”
Section: Discussionmentioning
confidence: 95%
“…As the net muscle force must exceed the load during shortening contractions and be less than the load during lengthening contractions, most studies have reported that discharge rate declines when lowering an inertial load but not when lifting the load (Del Valle and Thomas, 2005;Kallio et al, 2013;Laidlaw et al, 2000;Semmler et al, 2002;Søgaard, 1995;Stotz and Bawa, 2001;Tax et al, 1989). A similar behaviour was observed when resisting instead of assisting a torque motor for a comparable change either in relative force (Altenburg et al, 2009) or in absolute force and fascicle length between the anisometric contractions (Pasquet et al, 2006).…”
Section: Muscle Activation During Submaximal Contractionmentioning
confidence: 87%
“…This selective recruitment of high-threshold motor units ( presumably fastcontracting muscle units) during the lengthening contractions occurred most often at faster angular velocities, which led Nardone and colleagues (1989) to suggest that such changes in task requirements may involve an adjustment in the recruitment order of motor units. Although another paper reported the occasional selective recruitment of high-threshold motor units (3 out of 21 units) in the first dorsal interosseous when lifting and lowering submaximal inertial loads (∼15% MVC force; Howell et al, 1995), most subsequent studies have not found any systematic differences in motor unit recruitment between anisometric contractions when lifting and lowering relatively light inertial loads (≤20% MVC force; Bawa and Jones, 1999;Garland et al, 1996;Laidlaw et al, 2000;Søgaard, 1995;Søgaard et al, 1996;Stotz and Bawa, 2001) or assisting and resisting a torque motor with submaximal forces (≤50% of maximum; Altenburg et al, 2009;Pasquet et al, 2006;Stotz and Bawa, 2001).…”
Section: Muscle Activation During Submaximal Contractionmentioning
confidence: 98%
See 2 more Smart Citations